Epigenetic Alterations in Human Liver From Subjects With Type 2 Diabetes in Parallel With Reduced Folate Levels - Nilsson, Emma; Matte, Ashok; Perfilyev, Alexander; de Mello, Vanessa D.; Käkelä, Pirjo; Pihlajamäki, Jussi; Ling, Charlotte (The journal of clinical endocrinology and metabolism, 2015)
Objective:Epigenetic variation may contribute to the development of complex metabolic diseases such as type 2 diabetes (T2D). Hepatic insulin resistance is a hallmark of T2D. However, it remains unknown whether epigenetic alterations take place in the liver from diabetic subjects. Therefore, we investigated the genome-wide DNA methylation pattern in the liver from subjects with T2D and nondiabetic controls and related epigenetic alterations to gene expression and circulating folate levels.Research Design and Methods:Liver biopsies were obtained from 35 diabetic and 60 nondiabetic subjects, which are part of the Kuopio Obesity Surgery Study. The genome-wide DNA methylation pattern was analyzed in the liver using the HumanMethylation450 BeadChip. RNA expression was analyzed from a subset of subjects using the HumanHT-12 Expression BeadChip.Results:After correction for multiple testing, we identified 251 individual CpG sites that exhibit differential DNA methylation in liver obtained from T2D compared with nondiabetic subjects (Q < .05). These include CpG sites annotated to genes that are biologically relevant to the development of T2D such as GRB10, ABCC3, MOGAT1, and PRDM16. The vast majority of the significant CpG sites (94%) displayed decreased DNA methylation in liver from subjects with T2D. The hypomethylation found in liver from diabetic subjects may be explained by reduced folate levels. Indeed, subjects with T2D had significantly reduced erythrocyte folate levels compared with nondiabetic subjects. We further identified 29 genes that displayed both differential DNA methylation and gene expression in human T2D liver including the imprinted gene H19.Conclusions:Our study highlights the importance of epigenetic and transcriptional changes in the liver from subjects with T2D. Reduced circulating folate levels may provide an explanation for hypomethylation in the human diabetic liver.